2014
DOI: 10.1007/s00068-014-0439-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of traumatic deaths in a level one trauma center in Ankara, Turkey

Abstract: Trauma management shows significant progress in last decades. Determining the time and place of deaths indicate where to focus to improve our knowledge about trauma. We conducted this retrospective study from data of trauma victims who were brought to a major tertiary hospital which is a level one trauma center in Ankara, Turkey, and died even if during transport or in the hospital between 1 March 2010 and 1 March 2013. The patients' demographic characteristics, trauma mechanisms, time frames and causes of dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
34

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 16 publications
1
6
0
34
Order By: Relevance
“…Güloğlu et al reported that the most common cause of urogenital injury is traffic accidents [7]. Arslan et al in their study stated that the most frequently injuries are seen due to traffic accidents [12]. Our results are consistent with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Güloğlu et al reported that the most common cause of urogenital injury is traffic accidents [7]. Arslan et al in their study stated that the most frequently injuries are seen due to traffic accidents [12]. Our results are consistent with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…4 In the last decade, Turkey has been focusing on improving its emergency medical care system that also provides trauma care. 5 Despite studies that have assessed the causes of traumatic deaths in Turkey and the need to improve overall trauma care, 6 the required components of level I trauma centers, such as providing leadership in trauma prevention and public education, providing training of the trauma team members, building a systematic teaching and research effort system to direct new innovations in trauma care, developing new strategies based on a trauma database, and others 7 are still lacking. Trauma mortality rates in the Turkish trauma system are higher when compared with the mortality rates reported by trauma centers in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Trajano ve arkadaşları en sık travmatik ölüm sebebinin araç dışı trafik kazası olduğunu bildirmişlerdir 11. Arslan, Evans ve arkadaşları travmatik ölümlerin sırasıyla %44 ve %72 oranında motorlu taşıt kazası sonucu olduğunu tespit etmişlerdir 9,13. Gunst ve arkadaşları ise farklı olarak travmaya bağlı ölümlerin en sık sebebinin ateşli silah yaralanması olduğunu bildirmişlerdir 12.…”
unclassified
“…Çalışmamızda başvurusunda arrest olan hastaların 71'inde ve arrest olmayanların 43'ünde baş-boyun yaralanması mevcuttu. Arslan ve arkadaşları travmaya bağlı ölümlerde en sık nedenin travmaya bağlı beyin yaralanması olduğunu bildirmişlerdir 9. Trajona, Gunst, Hamzeh ve arkadaşları travmaya bağlı ölümlerde en sık nedenin kafa travması olduğunu bildirmişlerdir 11,12,14.…”
unclassified